Impact of wood cuts on the structure and floristic diversity of vegetation in the peri-urban zone of Ngaoundere, Cameroon - Tchobsala; Amougou Akoa; Mbolo Marie (African Journal of Environmental Economics and Management, 2022)
The main objective of this paper was to study the impact of various wood cuts on the structure and the floristic diversity of the savannas, and to seek for durable solutions against deforestation during a four year investigation. An inventory of the woody layer on 120 sites areas of 50 × 50 m showed that savannas have structures in "L". This structure translate the state of the degradation of the vegetation. The floristic diversity showed that the characteristic species of the degradation of the shrubby savannas area are Hymenocardia acida, Piliostigma thonningii and Annona senegalensis, and those of the wooded savannas are Daniellia oliveri and Cesalpinia sp. It was also shown that highest wood cuts are depressive for the stability of the savannas and for the disappearance of the vegetable biodiversity. Consequently, they are responsible for the acceleration of the degradation and the alarming installation of the desert in wet savannas of Ngaoundéré. A measure of co-administration between the government and the bordering population must be therefore encouraged to protect and safeguard the anthropized vegetation.